Biodiversity and Protected Areas - Baldwin, Robert; Beazley, Karen (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Biodiversity and Protected Areas assembles twelve topics from around the world, illustrating the complexities and promise of addressing the biodiversity crisis. Authors from Mongolia, Africa, India, Canada, Iraq, and the United States dwell on particular aspects and challenges relevant to those regions. Lessons and approaches from interesting localities, coupled with global analyses give the reader a synthetic view of emerging problems. The opportunities for understanding common issues across different geographies abound, such as comparing local conservation in sub-Saharan Africa with a distribution of very small protected areas in Massachusetts. Several topics will be of immediate interest to policymakers. The book is illustrated with numerous color maps and figures and the authors strove for clear, uncomplicated writing. The editors provide an overview of chapters, placing them in the context of other biodiversity and protected area literature. Students and conservationists attempting to broaden their views of biodiversity and protected areas should find this collection to be interesting.